Parsing the Source: From Form to Light, From Known to Knowing, From Substance to Void - Engstrom, Jack (Cosmos and History: The Journal of Natural and Social Philosophy, 2016)
<!--[if gte mso 9]> <![endif]--> Portions of Arthur M. Young's Theory of Process and G. Spencer-Brown's Laws of Form (LoF) are presented as deep (ultimate) ontic and epistemic ways, respectively, to parse the Universe and our experience into parts of wholes: both systems include the observer/experiencer/agent as an integral part of the Universe, with a partial unity of knower and known. In Young's theory, the Universe is generated by dividing Wholeness: into three, creating substance; and into four, creating form; and their combination, giving the formed substance of molecular matter. (Then from matter, Life acquires powers, in stages.) Reversing the sequence of generation gives an ontic parsing into Wholeness and its divisions. Spencer-Brown's neoPlatonic ontology has radiant Being at its ontic center, with existence at its periphery (or surface), and has at its epistemic center a knowing being. The epistemology of LoF deconstructs our knowledge of existence to successively-more-central fields: of truth, then of indications, then of The Form of some first distinction, and finally to a Void which can include a knowing being. This deconstruction has an analogy in ‘retracting ones psychological projection', resulting in liberating self-realization. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->